Thai Traditional Herbal Medicines Used to Treat Paresis and Paralysis in Tamra Kanphaet Thaidoem (Phaetthayasat Songkhro Chabap Anurak) Volume 1: An Analysis Based on Thai Traditional Pharmacy and Their Scientific Evidences - ฺBooranasubkajorn Suksalin; Prathumsuwan, Nunthawan; Henggrathock, Pornnatcha; Harnphadungkit, Kamontip; Akarasereenont, Pravit; Khatshima , Kangvol (Siriraj Medical Bulletin, 2021)
Objectives: To study herbal medicines used to treat paresis and paralysis in Tamra Kanphaet Thaidoem (Phaetthayasat Songkhro Chabap Anurak) Volume 1, to analyze the medicinal tastes of herbal medicines and herbal formulae and to review scientific evidence related to the treatment of paresis and paralysis property of the herbs Methods: This research is qualitative. Herbal recipes and herbs mentioned for the treatment of paresis and paralysis in the Thai traditional medicine scriptures were listed. The names of crude drugs and their medicinal tastes were checked by experts. Then the literature search was performed using PubMed and Google scholar databases to find scientific evidence related to the treatment of paresis and paralysis property on the crude drugs. Results: Eight out of thirteen scriptures mentioned remedies for paresis and paralysis. Khamphi Sapphakhunya and Khamphi Thatwiphang contained the highest number of herbal recipes (5 recipes) followed by Khamphi Roknithan (4 recipes). The paresis and paralysis remedies included 8 single herbs and 22 herbal recipes. The 22 herbal recipes consist of 142 herbs. Twenty-two herbs have been used in more than 4 formulas. The most used herb is Piper nigrum L. The most common medicinal taste in descending order was hot taste 26.32 %, salty 14.47 %, and bitter 13.16 %. The literature search provided pharmacological activity evidence related to the traditional uses of 19 herbs such as antiplatelet and neuroprotective effect. Conclusion: The paresis and paralysis were mentioned in many scriptures of Thai traditional medicine. The use of herbal recipes is more common than single herbs. The lack of scientific evidence suggests that there is a crucial need for research on these remedies to provide rational uses.